2021
DOI: 10.1371/journal.pbio.3001464
|View full text |Cite
|
Sign up to set email alerts
|

A crowdsourcing open platform for literature curation in UniProt

Abstract: The UniProt knowledgebase is a public database for protein sequence and function, covering the tree of life and over 220 million protein entries. Now, the whole community can use a new crowdsourcing annotation system to help scale up UniProt curation and receive proper attribution for their biocuration work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(69 citation statements)
references
References 8 publications
(9 reference statements)
0
50
0
1
Order By: Relevance
“…Mogroside V-linked targets were identified using the Swiss Target Prediction, PharmMapper, and Batman databases. Targets of drug action were screened after review (Swiss-Prot) for target correction using the UniProt database ( 19 ). GeneCards, DrugBank, Online Mendelian Inheritance in Man (OMIM) ( 20 ), and therapeutic target databases searched for COVID-19 and ovarian cancer-related targets.…”
Section: Methodsmentioning
confidence: 99%
“…Mogroside V-linked targets were identified using the Swiss Target Prediction, PharmMapper, and Batman databases. Targets of drug action were screened after review (Swiss-Prot) for target correction using the UniProt database ( 19 ). GeneCards, DrugBank, Online Mendelian Inheritance in Man (OMIM) ( 20 ), and therapeutic target databases searched for COVID-19 and ovarian cancer-related targets.…”
Section: Methodsmentioning
confidence: 99%
“…3D structures of HIV proteins (gp120 and integrase) were also retrieved from RCSB Protein Data Bank [30] . From the uniport database [36] annotations (accessed on: 21/06/22), we found that the surface protein gp120 is a part of envelope glycoprotein gp160 (PDB id: 3J70). So, we considered the sequence range corresponding to gp120 (33–511) for further analysis.…”
Section: Methodsmentioning
confidence: 99%
“…UniProt ( https://www.uniprot.org ) provides information on chemical substances and biological activities. We make a decision to eliminate some chemicals after the replicated data is deleted due to the lack of accurate structural information of the targets of the compounds, which is unable to be forecasted successfully [ 35 , 36 ] ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%